The Potency of Tissue Thromboplastic Suspensions - Gollub, Seymour; Ottolenghi, Abramo C.; Lisbinsky, Lenore; Uin, Alex W. (Thrombosis and Haemostasis, 1962)
The potency of various human brain thromboplastic suspensions was estimated by two independent test systems. It was found that potency estimation using the in vitro system (clot acceleration) did not correlate with potency estimation of an in vivo system (thrombotic-lethal). However, good correlation between lethality and thromboplastinase labile phospholipid compartment was established. These findings are briefly discussed.